Phylogenetic reconciliation provides new insights into the evolutionary diversification of the glutamine synthetase gene family in seed plants. - Aledo, Elena; Cañas-Pendón, Rafael Antonio; Ruiz-Canton, Francisco Javier; Aledo-Ramos, Juan Carlos (Wiley, 2025)
Glutamine synthetase (GS) catalyzes the incorporation of ammonium into glutamate, a crucial reaction in nitrogen metabolism. Despite advances in plant genomics, the evolutionary relationships among GS isoforms in seed plants remain incompletely understood. In this study, we selected 155 GS genes from 45 phylogenetically well-characterized seed plant species. Our analyses consistently support the existence of three distinct evolutionary lineages of GS genes in seed plants: GS2 (chloroplastic), and GS1a and GS1b (cytosolic). Using a Bayesian molecular clock dating approach, we estimate that GS2 diverged approximately 560 million years ago, whereas GS1a and GS1b began to diverge around 70 million years later. Additionally, we developed ORTHGS, a software tool that implements tree reconciliation and enables analyses of orthology and paralogy among GS enzymes. Phylogenetic reconciliation offers new insights into the evolutionary dynamics of the GS gene family in plants, revealing the existence of new paralogs of GS1a and GS2. Most of the genomes analyzed contain multiple paralogs of GS1b, whereas GS1a and GS2 appear as singleton genes. Although these single-copy genes have traditionally been considered orthologs, we present evidence challenging this assumption. Thus, our findings suggest that both GS1a and GS2 have undergone multiple duplication events throughout evolutionary history, similar to GS1b. However, unlike GS1b, only a single paralog of GS1a (or GS2) is retained per genome. Overall, our study reshapes the understanding of GS gene family evolution in seed plants by uncovering hidden duplication events in GS1a and GS2, highlighting dynamic evolutionary patterns previously overlooked in this gene family.
Keywords: Genética vegetal; Fanerógamas; Glutamina; Enzimas; Filogenia; Evolución (Biología); Phylogenetic reconciliation; Glutamine synthetase; Gene family; Evolution; Seed plants